The Importance of Quality Control for The Success of A Company - Zacharias, Mayang (Asian Journal of Logistics Management, 2022)
Quality control is an important part of the company’s production process, especially for manufacturing companies. Quality control itself is a comprehensive process that needs to be upheld by the company to make sure it has quality products. This article aims to provide enrichment about quality management, quality control, the process, the approach, as well as the tools gathered from diverse sources. Information from journals, books, and others was first gathered and combined to produce a comprehensive and full understanding of the topic. This article helps to provide a better understanding of quality control, however, it is necessary to explore the examples that have been applied by various companies.